Meningkatkan Mutu Lulusan Melalui Implementasi Praktik Kerja Lapangan - Defris Hanindya Edwiyan Pradana; Yoto Yoto; Amat Nyoto (Graduate School of Universitas Negeri Malang, 2021)
Abstract: The purpose of this article is to explain the implementation of field work practices ranging from planning, implementation, and evaluation at VHS Islam 1 Blitar. This article uses qualitative methods and the type of research is case studies. The results of the research obtained about the implementation of fieldwork at VHS Islam 1 Blitar have been going well. At the time the planning was prepared regarding the preparation of the school in establishing cooperation with industry, the assessment of the industry as the location of the field work practice, the preparation of the supervising teacher, the preparation of the instructor and student preparation, as well as the preparation of facilities and infrastructure to support the activity of the field work. At the implementation stage it has been carried out structurally and organized starting from the submission of students, placement of students, coaching, supervision processes and pickup students. In assessments that have been well implemented with reports on activities from schools and assessments from industry and granting certificates to students.Abstrak: Tujuan artikel ini adalah untuk menjelaskan implementasi praktik kerja lapangan mulai dari perencanaan, pelaksanaan, dan evaluasi di SMK Islam 1 Blitar. Artikel ini menggunakan metode kualitatif dan jenis penelitiannya adalah study case. Hasil penelitian yang didapatkan bahwa implementasi praktik kerja lapangan di SMK Islam 1 Blitar sudah berjalan dengan baik. Pada tahap perencanaan sudah disiapkan mengenai persiapan sekolah dalam menjalin kerja sama dengan industri, kriteria industri sebagai lokasi praktik kerja lapangan, persiapan guru pembimbing, persiapan instruktur dan persiapan siswa, serta persiapan sarana dan prasarana penunjang kegitan Praktik kerja lapangan. Pada tahap pelaksanaan sudah dilakukan secara struktural dan terorganisir mulai dari penyerahan siswa, penempatan siswa, pembimbingan, proses pengawasan, dan penjemputan siswa. Pada tahap evaluasi sudah diterapkan dengan baik dengan adanya penilaian laporan kegiatan dari sekolah dan penilaian dari industri serta pemberian sertifikat kepada siswa.